The alien within representations of the exotic in twentieth-century Japanese literature - Morton, Leith 1951- (Univ. of Hawaii Press, 2009)
"The Alien Within is the first book-length thematic study in English of the alien in modern Japanese literature and helps shed new light on a number of important authors. Leith Morton examines the Gothic, a form of writing with strong affinities to European Gothic and a motif in the fiction of several key modern Japanese writers, such as Arishima Takeo. Morton also discusses the translations of Tsubouchi Shoyo, Japan's most famous early translator of Shakespeare, and how this most alien and exotic author was absorbed into the Japanese literary and theatrical tradition. The new field of translation theory and how it relates to translating Shakespeare are also discussed. Morton devotes two chapters to the celebrated female poet Yosano Akiko, whose verse on childbirth and her unborn children broke taboos relating to the expression of the female body and sensibility. He also highlights the writing of contemporary Okinawan novelist Oshiro Tatsuhiro, whose work springs from what is for Japanese an exotic subtropical landscape and makes symbolic reference to the otherness at the heart of Japanese religiosity. Another significant but equally overlooked subject is the focus of the final chapter, which analyzes the travel writing of internationally best-selling author Murakami Haruki. Murakami's great corpus of work includes a one-volume study of the 2000 Sydney Olympics, which Morton discusses in detail." -- Book jacket.
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Japanese literature -- 20th century -- History and criticism; Exotik; Japanisch; Literatur